The effect of combined self- and expert-modelling on the performance of the double leg circle on the pommel horse - Baudry, L.; Leroy, D.; Chollet, D. (Journal of Sports Sciences, 2006)
In this study, we investigated whether video modelling can enhance gymnasts' performance of the circle on a pommel horse. The procedure associated expert-modelling with self-modelling and quantitative performance analysis. Sixteen gymnasts were randomly assigned to one of two groups: (1) a modelling group, which received expert- and self-modelling, and performance feedback, or (2) a control group, which received no feedback. After five sessions of training, an analysis of variance with repeated measures indicated that the gains in the back, entry, front, and exit phases of the circle were greater for the modelling group than for the control group. During the training sessions, the gymnasts in the modelling group improved their body segmental alignment during the back phase more quickly than during the other phases. As predicted, although both groups performed the same number of circles (300 in 5 days, with 10 sequences of 6 circles), the modelling group improved their body segmental alignment more than the control group. It thus appears that immediate video modelling can help to correct complex sports movements such as the circle performed on the pommel horse. However, its effectiveness seemed to be dependent on the complexity of the phase.